IMPLEMENTATION OF PROBLEM-BASED LEARNING MODELS SUPPORTED BY TRAINER RADIATOR MODULE FOR HEAT TRANSFER LEARNING - I Made Arsana; Sudirman Rizki Ariyanto; Hanif Gunawan Wibisono (Jurnal Taman Vokasi, 2019)
The purpose of this study is to analyze the increase in student learning outcomes in heat transfer learning that is taught using a problem-based learning model assisted by the radiator trainer module. This type of research is classroom action research. The technique of collecting data uses a test of learning outcomes consisting of tests of cognitive learning outcomes and psychomotor domains. Data analysis method uses descriptive analysis. The results of this study indicate that there is an increase in student learning outcomes after being learned using a problem-based learning model assisted by the radiator trainer module. It is proven that when compared with individual and classical completeness criteria > 80 in the first cycle the percentage of students who entered the complete category was only 25%. While in the second cycle the percentage of students who entered the complete category increased to 88%. When compared between the percentage of learning outcomes in the first cycle and second cycle, there was a significant increase with a percentage difference of 63%. Thus it can be concluded that the problem-based learning model supported by the radiator trainer module can help students improve the learning outcomes of heat transfer courses.